Mass communication : issues, perspectives and techniques - Detrani, Jason R., 1965- (Oakville, Ont. : Apple Academic Press, 2011)
Mass communication is the academic study of the various means by which individuals and entities communication information via mass media to large audiences at the same time. Mass communication channels include newspaper and magazine publishing, radio television and film, and of course, the internet.
Includes bibliographical references and index.
Keywords: Mass media; Mias